Inverse problem for the heat equation with degeneration - Ivanchov, N. I.; Saldina, N. V. (Ukrains’kyi Matematychnyi Zhurnal, 2005)
We consider the inverse problem of determining the time-dependent thermal diffusivity that is equal to zero at the initial moment of time. We establish conditions for the existence and uniqueness of a classical solution of the problem under consideration.